Relationship between systemic inflammatory response index and bone mineral density in children and adolescents aged 8-19 years: a cross-sectional study based on NHANES 2011-2016 - Cun, Dejun; Yang, Nan; Zhou, Lin; Zeng, Wenxing; Chen, Bin; Pan, Zichen; Feng, Huang; Jiang, Ziwei (Frontiers in Endocrinology, 2025)
ObjectiveThis study aims to investigate the relationship between the Systemic Inflammatory Response Index (SIRI) and bone mineral density (BMD) in children and adolescents aged 8-19 years.MethodsA cross-sectional design was used, utilizing NHANES data from 2011-2016, including 3,205 participants aged 8 to 19 years. Weighted multivariable regression analysis was conducted to assess the association between SIRI and BMD at the lumbar spine, pelvis, trunk, and whole body. Additionally, smooth curve fitting was applied to examine the nonlinear relationship between SIRI and BMD, and subgroup analyses were performed to explore potential interaction effects and modifiers.ResultsSIRI was significantly positively correlated with BMD at the pelvis, trunk, and whole body (p < 0.05). After adjusting for covariates, a one-unit increase in ln(SIRI) was associated with increases in BMD of 0.018 g/cm², 0.006 g/cm², and 0.005 g/cm² for the pelvis, trunk, and whole body, respectively. Nonlinear analysis revealed a saturation effect between ln(SIRI) and BMD, with a more pronounced impact at specific threshold values. Subgroup analysis indicated that gender, age, BMI and total calcium levels modulated the relationship between SIRI and BMD.ConclusionSIRI is significantly associated with BMD in children and adolescents, with a positive effect on BMD at specific threshold levels. This finding suggests that SIRI may serve as a potential biomarker for assessing the risk of low bone mineral density, offering theoretical support for the prevention and intervention of bone health issues such as osteoporosis.